Unusual Presentation of Mediastinal Neurogenic Tumours. (8th May 2013) - Negri, Giampiero; Bandiera, Alessandro; Carretta, Angelo; Puglisi, Armando; Mandelli, Carlo; Ciriaco, Paola; Zannini, Piero
Abstract : Mediastinal neurogenic tumours generally arise as single benign lesions and their typical location is the costovertebral sulcus. In about 10% of cases mediastinal neurogenic tumours may extend to the spinal canal; occasionally they may extend to the cervical region and, more rarely, may be multiple or associated with other synchronous mediastinal lesions. The treatment of choice is surgical resection. This report describes three cases of unusual presentation of mediastinal benign schwannomas successfully treated at our Hospital. In the first case multiple simultaneous paravertebral lesions were resected through a posterior approach. In the second case a tumour of the posterior mediastinum extending to the cervical region was excised through a one-stage combined supraclavicular incision followed by left mini-invasive video-assisted thoracoscopic surgical techniques. The third case describes a patient with a posterior neurogenic mediastinal tumour with a synchronous parathyroid adenoma of the anterior mediastinum, which were both successfully resected by video-assisted thoracoscopic surgery.